Evaluación de riesgos ergonómicos y su relación con los trastornos musculoesqueléticos en los trabajadores del área de bodega de Ecuacerámica - Valdivieso Noboa, German David (2025)
Workers in the finished product warehouse of Ecuacerámica are constantly exposed to ergonomic risk factors due to load handling, awkward postures, and repetitive movements. These working conditions significantly increase the likelihood of developing musculoskeletal disorders (MSDs). The main objective of this study was to evaluate the ergonomic risks of awkward postures using the OWAS method and lift loads using the NIOSH method so that workers could determine their relationship with musculoskeletal disorders. The results show that warehouse assistants, who are nine people, are at high risk of musculoskeletal injuries from lifting loads and from awkward postures when unloading products. The forklift operators, four people, face high ergonomic risks from awkward postures while operating machinery, but they are not at risk from lifting loads. The warehouse manager faces lower risks from awkward postures when controlling and working on the computer and no risks from lifting loads. Finally, the Nordic questionnaire found that two out of three warehouse workers experienced musculoskeletal discomfort in the past year, with the lower back being the most affected, accounting for 28.6%. In conclusion, corrective measures were proposed to reduce ergonomic risks in the warehouse area, prioritizing tasks that pose the most significant risk of musculoskeletal injuries due to awkward postures or lifting loads.